2008
DOI: 10.1021/es072013j
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Bacteria for Phytostabilization of Mine Tailings

Abstract: Eolian dispersion of mine tailings in arid and semiarid environments is an emerging global issue for which economical remediation alternatives are needed. Phytostabilization, the revegetation of these sites with native plants, is one such alternative. Revegetation often requires the addition of bulky amendments such as compost which greatly increases cost. We report the use of plant growth-promoting bacteria (PGPB) to enhance the revegetation of mine tailings and minimize the need for compost amendment. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 32 publications
1
80
0
1
Order By: Relevance
“…Bioremediation is recognized as an important tool to restore contaminated sites, reforest eroded areas, and restore degraded ecosystems. The plant is the major component of the phytoremediation processes, and application of microbial inoculants in bioremediation of contaminated soil and reforestation of degraded lands is a promising research area (deBashan et al 2010a;2010b;Grandlic et al 2008;Kuiper et al 2004;Ma et al 2011). Application of Kluyvera ascorbata increased several plant parameters and promoted plant growth of tomato, canola (Brassica napus), and Indian mustard (Brassica juncea) grown in soils containing high concentrations of zinc and nickel (Burd et al 2000).…”
Section: Emerging Areas Related To Microbial Inoculantsmentioning
confidence: 99%
“…Bioremediation is recognized as an important tool to restore contaminated sites, reforest eroded areas, and restore degraded ecosystems. The plant is the major component of the phytoremediation processes, and application of microbial inoculants in bioremediation of contaminated soil and reforestation of degraded lands is a promising research area (deBashan et al 2010a;2010b;Grandlic et al 2008;Kuiper et al 2004;Ma et al 2011). Application of Kluyvera ascorbata increased several plant parameters and promoted plant growth of tomato, canola (Brassica napus), and Indian mustard (Brassica juncea) grown in soils containing high concentrations of zinc and nickel (Burd et al 2000).…”
Section: Emerging Areas Related To Microbial Inoculantsmentioning
confidence: 99%
“…Plant growth promoting bacteria improve physicochemical and biological properties of poor, degraded substrates and make them more suitable for plants (Grandlic 2008, Karličić et al 2016) with simultaneous increase of plant survival and seedling quality, especially in soils with weak microbial activity (Chanway 1997, DominguezNuñez et al 2015. Positive outcomes of PGPB application are enhancement of seedlings emergence, faster plant growth, higher biomass production (Ribeiro & Cardoso 2012), increase of root length, and branching, increased leaf area, and chlorophyll content, and higher resistance to abiotic stresses (Glick 2012) as well as to pests or diseases (Cawoy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has explored the minimum compost amendment required for sustained plant growth (7,11,16). Significant incremental increases were observed in total plant biomass for plants grown in extremely (pH 2.7) and moderately (pH 5.7) acidic mine tailings amended with 0, 5, and 10% compost.…”
mentioning
confidence: 99%
“…Heterotrophic plate counts were used as a measure of soil health because previous phytostabilization research has demonstrated a positive relationship between these counts and final plant biomass (11). Both neutrophilic (pH 7) and moderately acidic (pH 5) heterotrophs were enumerated (7). Results showed that unamended T2 had low neutrophilic counts, (2.34 Ϯ 0.10) ϫ 10 3 (standard deviation; n ϭ 3), which increased by 1.5 and 2 log units, respectively, with the addition of 5% and 10% compost (Table 1).…”
mentioning
confidence: 99%